Intraocular pressure changes after phacoemulsification in pseudoexfoliation versus healthy eyes - Ramezani, Farshid (BMC Ophthalmol, 2021)
BACKGROUND: Pseudoexfoliation (PXF) syndrome is the most common cause of secondary glaucoma worldwide. This systemic disorder causes further damage to the optic nerve and ultimately increases the need for surgical interventions. Therefore, intraocular pressure (IOP) control is very important in these patients. The aim of this study was to compare IOP changes after phacoemulsification in subjects with PXF syndrome compared to those without this syndrome. METHODS: 61 patients were enrolled in this prospective clinical study. Subjects were assigned into two groups based on presence or absence of PXF syndrome. IOP and anterior chamber angle parameters including: angle opening distance (AOD) and trabecular-iris surface area (TISA) measured one day preoperatively and 3 months postoperatively. Intraoperative metrics factors including: infusion fluid usage (IFU), cumulative dissipated energy (CDE) and aspiration time (AT) were obtained from the phacoemulsification machine at the end of each surgery. IOP changes, anterior chamber angle parameters and intraoperative metrics factors were compared between groups. RESULTS: Mean IOP before surgery was significantly higher in the PXF group (14.70 mm Hg) compared to controls (12.87 mm Hg) (P-value < 0.01). Phacoemulsification decreased IOP in both, but to greater extent in the PXF group (p-value < 0.01). AOD and TISA also increased significantly following surgery in both groups. The results showed that postoperative IOP was negatively correlated with preoperative IOP in both groups (p-value < 0.01). Also, IOP after phacoemulsification was negatively correlated with IFU in the PXF group (p-value = 0.03). CONCLUSIONS: Patients with PXF syndrome exhibited a reduction in IOP and increase in anterior chamber angle parameters after phacoemulsification. We observed a greater IOP reduction in PXF subjects when it was compared to controls. Higher preoperative IOP and intraoperative IFU were associated with more IOP reduction in the PXF group.